2011
DOI: 10.1021/jo201437j
|View full text |Cite
|
Sign up to set email alerts
|

Hiyama Cross-Coupling of Arenediazonium Salts under Mild Reaction Conditions

Abstract: Palladium acetate [Pd(OAc)(2)]-catalyzed Hiyama cross-coupling of arenediazonium salts with organosilanes was found to generate biaryl products in high yields in alcoholic solutions. The simple and efficient protocol does not require any bases, ligands, or air/moisture. The transformation can tolerate either electron-donating or electron-withdrawing functional groups. Theoretical studies show that the transmetalation is the rate-limiting step for the cross-coupling reaction and both acetate and tetrafluorobora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 128 publications
0
75
0
1
Order By: Relevance
“…This poor yield may be due to steric hindrance. The thienyl and pyridinyl group survived well under the standard conditions, giving the corresponding products in moderate yields (Table 4, entries [13][14]. Importantly, structurally challenging nitrogen heterocyclic moiety in a number of bioactive natural products, such as oxazole and pyrimidine derivatives, were also coped with this conditions (Table 4, entries 15-16).…”
Section: Resultsmentioning
confidence: 95%
“…This poor yield may be due to steric hindrance. The thienyl and pyridinyl group survived well under the standard conditions, giving the corresponding products in moderate yields (Table 4, entries [13][14]. Importantly, structurally challenging nitrogen heterocyclic moiety in a number of bioactive natural products, such as oxazole and pyrimidine derivatives, were also coped with this conditions (Table 4, entries 15-16).…”
Section: Resultsmentioning
confidence: 95%
“…Pd(OAc) 2 , PdCl 2 , PdBr 2 and PdI 2 were somewhat effective, giving a 78%, 73%, 71% and 74% yield of 4-methyl-1,1'-biphenyl (entries 4-7). Other palladium(II) compounds with phosphine ligands led to higher amounts of desired products (entries [8][9][10][11], and the denitrogenative coupling was inhabited with Pd (0) catalysts (entries 12-13). To our delight, Pd(CH 3 CN) 2 Cl 2 served as a catalyst to afford the desired biaryl products in 89% yield (entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Qi and coworkers reported a practical carbon-nitrogen bond cleavage procedure for the Hiyama cross-coupling reactions using arenediazonium salts as the electrophilic reagents. 10 Notably, aryl diazonium salts are required to be freshly prepared and need to be kept in storage under zero degree. 11…”
Section: Introductionmentioning
confidence: 99%
“…A computational study by Qi and co-workers suggested that in addition to the acetate anion, also a weakly coordinating tetrafluoroborate anion might coordinate the silane and assist in the transmetallation step of Hiyama coupling. 209 3.1.6. Negishi Coupling.…”
Section: Stille Couplingmentioning
confidence: 99%